Peri-implantation 6PPD-Q exposure impairs endometrial decidualization and induces pregnancy loss - Wanting Fu; Ziyao Yang; Yi Li; Tianxiao Chen; Qingling Yang; Linli Hu (Journal of Hazardous Materials, 2026)

Portulaca Oleracea polysaccharides attenuate zearalenone-induced macrophage activation and Leydig cell dysfunction in testis: A single-cell and multi-omics study - Bingxin Huangfu; Yanan Chen; Jie Li; Ranyue Xu; Yijia Zhao; Linli Cheng; Xiaoyun He; Kunlun Huang (Food Research International, 2026)

The first toxicological assessment of copper exposure in Cipangopaludina cathayensis: Integrative insights from gut microbiota and hepatopancreas responses - Linli Li; Jinyou Wei; Yufan Deng; Jing Yu; Xiayun Wei; Weiying Wang; Jiamin Chen; Jing Wei; Tiantian Yuan; Haizhen Tan; Zhengjun Wu; Jiaoyun Jiang (Environmental Pollution, 2026)

Creating precise Cd(II)-targeted site through bioinspired tannic acid-modified coal gangue-derived zeolite for enhancing Cd(II) immobilization from aqueous solutions - Yuzhi Zhou; Linli Long; Jingyu Sun; Zongyao Li; Jingwei Niu; Jinming Duan; Min Chen; Boyu Wang; Xiaoyang Chen (Process Safety and Environmental Protection, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Plasma proteomic biomarkers as mediators for the associations between frailty phenotypes and chronic respiratory diseases - Yujia Bao; Shenghao Yuan; Jiawei Gu; Chen Shen; Linli Chen; Yibin Zhou; Jinjun Ran (GeroScience, 2026)
Frailty, a hallmark of systemic vulnerability in aging populations, is increasingly recognized in the clinical management of chronic respiratory diseases (CRDs). Molecular mechanism underpinning the relationships remain insufficiently elucidated. This study hence aimed to investigate whether proteomic biomarkers—circulating plasma proteins reflecting systemic inflammation, metabolism, and tissue remodeling—are associated with CRDs and may serve as potential mediators of the observed links. We analyzed data from a population-based cohort of 22,802 adults with proteomic measurements. Frailty was assessed by three phenotypes, including frailty index, physical frailty, and psychological frailty. Related-proteomic signatures were estimated by both linear and elastic regression models. Cox regression models were applied to explore the associations of frailty phenotypes and their proteomic signatures with incident CRDs, including asthma, chronic obstructive pulmonary disease (COPD), and idiopathic pulmonary fibrosis (IPF), as well as lung function outcomes, with full adjustments for potential confounders. Furthermore, mediation analyses were conducted to explore underlying mechanisms, complemented by pathway enrichment analyses to reveal relevant biological functions. Over a median follow-up of 13.2 years, 617 participants developed asthma, 701 developed COPD, and 228 developed IPF. Higher frailty index was associated with elevated risks of asthma (HR 1.95, 95% CI 1.64 to 2.31) and COPD (2.02, 1.71 to 2.38). Corresponding proteomic signature also related to increased risks of asthma (HR 1.22, 1.11 to 1.34) and COPD (1.65, 1.53 to 1.78). Mediation analysis suggested that the frailty index partially mediated the association with COPD, accounting for 26.0% (95% CI: 18.7 to 37.5%) of the total effect, respectively, particularly for GDF15, WFDC2, and PLAUR. Pathway enrichment analysis showed that these mediating proteins were predominantly involved in immune activation, inflammatory signaling, and metabolic stress responses. Frailty phenotypes contribute to elevated CRDs risks, partly through proteomic dysregulation in inflammatory and metabolic pathways. Graphic Abstract

Polystyrene nanoplastics induce ovarian injury by PI3K-Akt pathway-driven macrophage extracellular trap formation - Yingying Chen; Linli Yang; Yuanyuan Li; Lulu Si; Hanlin Fu; Tianjiao Lai; Ruixia Guo (Environmental Pollution, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Natural-product repurposing for novel reactive oxygen species inducer discovery: bactericidal profiling and structure-activity relationship of ellipticine and its analogs - Jingsha Yang; Guoqing Wang; Yi He; Wan Chen; Hongwu Liu; Linli Yang; Dan Zeng; Zhibing Wu; Liwei Liu; W.M.W.W. Kandegama; Zhenbao Luo; Xiang Zhou; et al. (Physiological and Molecular Plant Pathology, 2025)

Heterogeneous Rb-Sr isotopes in Chang’e-5/6 soils: implication for geochemical study of extraterrestrial samples - Le Zhang; Guanhong Zhu; Zhiming Chen; Jingyou Chen; Yan-Qiang Zhang; Zexian Cui; Chengyuan Wang; Haiyang Xian; Xianglin Tu; Jintuan Wang; Qing Yang; Ya-Nan Yang; et al. (Science Bulletin, 2025)

Efficient activating peracetic acid by copper-aluminum composites to degrade sulfathiazole: The critical role of Cu(III) species - Yuxiao Mu; Yanping Ding; Linli Tan; Qiulin Shi; Lei Chen; Jiaqi Ding; Jingwen Wang; Yong Liu; Pengchao Xie (Journal of Environmental Chemical Engineering, 2025)

Effect of the new fixed-time artificial insemination technology based on novel hormone preparations in gilts - Kexiong Liu; Hanbing Zhang; Xiaoling Xu; Zheng Huang; Feng Ji; Yusheng Qin; Linli Xiao; Shiwen Chen; Miaomiao Yan; Peng Zhao; Suozi Ge; Jiani Shu; et al. (Animal Reproduction Science, 2025)

Impact of pivot selection and lexicon utilization on pivot profile analysis of food off-odor reduction: The case of soymilk - Chang Liu; Linli Bu; Chen Wang; Hongwei Wang; Huayi Suo (Food Quality and Preference, 2025)

OsBSK3 and OsBSK2 regulate grain size and leaf angle via MAPK signaling pathway in rice - Xin Jin; Linli Fu; Chunxiao Chen; Jiali Liu; Yingxiang Liu; Wei Zhang; Xiufeng Li; Changhua Liu; Qingyun Bu; Xiaojie Tian (Theoretical and Applied Genetics, 2025)

Based on the resting-state functional magnetic resonance imaging reveals the causal relationship between the brain function network and the risk of tinnitus: a bidirectional Mendelian randomization analysis - Yuchao Liu; Chunli Li; Linli Yao; Yuan Tan; Lu Shi; Pei Chen (Brain Imaging and Behavior, 2025)

Arsenic exposure accelerates type 1 diabetes mellitus progression via pyroptosis pathway in mice - Lichao Lei; Mengling Chen; Chuan Qin; Linli Cai; Bing Liang (Chemico-Biological Interactions, 2025)

Construction and experimental verification of wave velocity model for source location in goaf overlying rock strata - Linli Zhou; Baoxin Jia; Xinyang Bao; Hao Chen; Kenan Zheng (Journal of Applied Geophysics, 2024)

HRD1 reduction promotes cholesterol-induced vascular smooth muscle cell phenotypic change via endoplasmic reticulum stress - Linli Wang; Zhitao Ren; Lin Wu; Ximei Zhang; Min Wang; Haiming Niu; Xuemin He; Heting Wang; Yanming Chen; Guojun Shi; Xiaoxian Qian (Molecular and Cellular Biochemistry, 2024)

Improving the value of planting and breeding waste compost in agricultural applications: A zucchini cultivation case and circular agricultural models analysis - Jianzhong Tie; Xueqin Gao; Yayu Liu; Wenxu Chen; Linli Hu; Jihua Yu; Tianlai Li (Chemical Engineering Journal, 2024)

Citrus transcription factor CsERF098 cooperates with CsWRKY70 to participate in response of fruit to green mold - Ting Li; Wenjun Wang; Qi Chen; Ou Chen; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Ionic liquid for selective extraction of lithium ions from Tibetan salt lake brine with high Na/Li ratio - Rujie Li; Yangyang Wang; Linli Chen; Wenjing Duan; Zhongqi Ren; Zhiyong Zhou (Desalination, 2024)

Teriflunomide Promotes Blood–Brain Barrier Integrity by Upregulating Claudin-1 via the Wnt/β-catenin Signaling Pathway in Multiple Sclerosis - Yipeng Zhao; Chen Chen; Xiuqing Xiao; Ling Fang; Xi Cheng; Yanyu Chang; Fuhua Peng; Jingqi Wang; Shishi Shen; Shilin Wu; Yiying Huang; Wei Cai; et al. (Molecular Neurobiology, 2024)

Prediction of the temporal and spatial evolution of subsidence waters in the Huainan mining area based on the CA–Markov model - Xuyang Zhang; Xiaoyang Chen; Yuzhi Zhou; Yongchun Chen; Linli Long; Pian Hu (Environment, Development and Sustainability, 2024)

Polybrominated diphenyl ethers in dust, hair and urine: Exposure, excretion - Junjie Jiang; Tianwei Li; Erde Wang; Yan Zhang; Jiali Han; Linli Tan; Xiang Li; Yuhao Fan; Ye Wu; Qianhui Chen; Jun Jin (Chemosphere, 2024)

B-N bonds between SrBi2B2O7 and humic acid composites enhance polarized electric field for efficient piezocatalytic degradation of oxytetracycline in water - Mude Zhu; Yi Tang; Xueqin Chen; Linli Xu; Xiaoyun Fan (Chemical Engineering Journal, 2024)

Adsorption Optimization of Methylene Blue from Aqueous Solution by Cost-Effective Biochar Using Response Surface Methodology and a Modeling Approach - Rui Duan; Yongchun Chen; Yuzhi Zhou; Linli Long; Zhiyang Jiang; Xiaoyang Chen (Water, Air, & Soil Pollution, 2023)

Prediction of the spatiotemporal evolution of vegetation cover in the Huainan mining area and quantitative analysis of driving factors - Xuyang Zhang; Yuzhi Zhou; Linli Long; Pian Hu; Meiqin Huang; Yongchun Chen; Xiaoyang Chen (Environmental Monitoring and Assessment, 2023)

OsUGE1 is directly targeted by OsGRF6 to regulate root hair length in rice - Shuaiqi Yang; Nuo Xu; Nana Chen; Jiaxuan Qi; Abdul Salam; Junyu Wu; Yihua Liu; Linli Huang; Bohan Liu; Yinbo Gan (Theoretical and Applied Genetics, 2023)

A self-regulated transcription factor CsWRKY33 enhances resistance of citrus fruit to Penicillium digitatum - Wenjun Wang; Ting Li; Jialin Chen; Xuan Zhang; Linli Wei; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Transcription factor CsERF1B regulates postharvest citrus fruit resistance to Penicillium digitatum - Ting Li; Wenjun Wang; Qi Chen; Jialin Chen; Xuan Zhang; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2023)

An empirical exploration into the determinants of rice farmers’ decisions to adopt low-carbon agricultural technologies in Hubei Province, China - Linli Jiang; Yun Tian; Nan Chen; Yun Luo (Mitigation and Adaptation Strategies for Global Change, 2023)

Simulation of land use trends and assessment of scale effects on ecosystem service values in the Huaihe River basin, China - Xuyang Zhang; Yuzhi Zhou; Linli Long; Pian Hu; Meiqin Huang; Wen Xie; Yongchun Chen; Xiaoyang Chen (Environmental Science and Pollution Research, 2023)

Toxicologic, transcriptomic, and metabolomic insights into the effect of a mixture of 26 veterinary antimicrobials on rat liver - Yehui Luan; Junjie Zhao; Yanan Chen; Jianzhong Shen; Linli Cheng (Chemosphere, 2023)

Genome-wide identification of the CsPAL gene family and functional analysis for strengthening green mold resistance in citrus fruit - Linli Wei; Wenjun Wang; Ting Li; Ou Chen; Shixiang Yao; Lili Deng; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Enhancing thermostability and activity of sucrose phosphorylase for high-level production of 2-O-α-d-glucosylglycerol - Linli Yang; Lukasz Peplowski; Yujuan Shen; Haiquan Yang; Xianzhong Chen; Wei Shen; Yuanyuan Xia (Systems Microbiology and Biomanufacturing, 2022)

Analysis of spatial and temporal changes of vegetation cover and its driving forces in the Huainan mining area - Xuyang Zhang; Ying Liu; Xiaoyang Chen; Linli Long; Yongdong Su; Xiaokun Yu; Hongmei Zhang; Yongchun Chen; Shikai An (Environmental Science and Pollution Research, 2022)

Connective profiles and antagonism between dynamic and static connectivity underlying generalized epilepsy - Sisi Jiang; Hechun Li; Haonan Pei; Linli Liu; Zhiliang Li; Yan Chen; Xiangkui Li; Qifu Li; Dezhong Yao; Cheng Luo (Brain Structure and Function, 2021)

Mycorrhizal fungal community composition in seven orchid species inhabiting Song Mountain, Beijing, China - Yanhong Chen; Yue Gao; Linli Song; Zeyu Zhao; Shunxing Guo; Xiaoke Xing (Science China Life Sciences, 2019)

Production of Brassica tri-genomic vegetable germplasm by hybridisation between tuber mustard (Brassica juncea) and red cabbage (B. oleracea) - Junxing Li; Linli Rao; Qiufeng Meng; Muhammad Awais Ghani; Liping Chen (Euphytica, 2015)

Effects of breeds and dietary protein levels on the growth performance, energy expenditure and expression of avUCP mRNA in chickens - Qihua Li; Zhiqiang Xu; L. Liu; Hongxin Yu; Hua Rong; Linli Tao; Xi Zhang; Xiaobo Chen; Dahai Gu; Yueyuan Fan; Xiaoqin Li; Changrong Ge; et al. (Molecular Biology Reports, 2013)

Detection of Bifidobacterium Species-specific 16S rDNA Based on QD FRET Bioprobe - JunFeng Jiang; ZhiHui Peng; Le Deng; Guang Li; LinLi Chen (Journal of Fluorescence, 2010)